PENGARUH TRANSPARANSI, AKUNTABILITAS, DAN PARTISIPASI TERHADAP PENGELOLAAN DANA DESA - Rifka Abdullah; Hartati Tuli; Nilawaty Yusuf (Oikos Nomos: Jurnal Kajian Ekonomi dan Bisnis, 2026)
Due to the discrepancy between the budget plan and the actual procurement realization, as well as the weak implementation of transparency and accountability mechanisms in village fund management, this study aims to analyze the influence of transparency, accountability, and community participation on village fund management in Tibawa District, Gorontalo Regency. This study employed a quantitative approach. The research population consisted of all village officials in Tibawa District, Gorontalo Regency. The sample was selected using a purposive sampling technique with a total of 50–100 respondents. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS 16. The results of the analysis indicate that partially, transparency has a significant effect on village fund management, accountability has no significant effect on village fund management, and community participation has a significant effect on village fund management. Simultaneously, the three variables significantly affect village fund management. The coefficient of determination value was 0.434, indicating that transparency, accountability, and community participation are able to explain 43.4% of village fund management, while the remaining percentage is influenced by other factors outside this study.